12(1+6d)=expand

Simple and best practice solution for 12(1+6d)=expand equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(1+6d)=expand equation:


Simplifying
12(1 + 6d) = expand
(1 * 12 + 6d * 12) = expand
(12 + 72d) = expand

Solving
12 + 72d = adenpx

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1adenpx' to each side of the equation.
12 + -1adenpx + 72d = adenpx + -1adenpx

Combine like terms: adenpx + -1adenpx = 0
12 + -1adenpx + 72d = 0

Add '-12' to each side of the equation.
12 + -1adenpx + -12 + 72d = 0 + -12

Reorder the terms:
12 + -12 + -1adenpx + 72d = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -1adenpx + 72d = 0 + -12
-1adenpx + 72d = 0 + -12

Combine like terms: 0 + -12 = -12
-1adenpx + 72d = -12

Reorder the terms:
12 + -1adenpx + 72d = -12 + 12

Combine like terms: -12 + 12 = 0
12 + -1adenpx + 72d = 0

The solution to this equation could not be determined.

See similar equations:

| 8x+3=70 | | (x^2)=38 | | 5(n+2)-3=22 | | x^2+27x+28= | | 2/7x+1/2x=3/5x+1 | | 24x-8-13x+2=24x-6-13x+11 | | 1=4x-5x+8 | | -4x-9-x=-9 | | 7(y-4)-7= | | 6-5x=8x | | y/6+22=2y | | 4^3(8^1/3z^2) | | C=12m+(4m-10) | | -23+x=x+11 | | -7(3q-1)=expand | | 5x+76x=105 | | 2y+4+3y-5+y=29 | | 0.88*x=22 | | z^2+12=48 | | log(128)4=x | | (3x)^2/3=0 | | 18-x/3=16 | | (x^2)=80 | | (3x-2)^2/3=16 | | -(4/7)-(1/5) | | x+2/13=9/13 | | (x^2)=-45 | | 2w^3-32w^2+6w-16= | | -4-7V=-26/3 | | 6.27=y/2.5-9.8 | | (6e+4*64)*500/63 | | -5/8/6 |

Equations solver categories